2019
DOI: 10.1016/j.nmni.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Der p 5 allergen from house dust mite: first epitope mapping of rabbit IgG blocking antibodies

Abstract: Der p 5 is one of the important house dust mite allergens in Algeria; this allergen is frequently recognized by patients with allergic asthma. However, there is no information on its IgG–binding epitopes. In the present study, rabbits were immunized with recombinant Der p 5 allergen, and serum samples were obtained. Recognition of linear IgG epitopes of Der p 5 was determined using synthesized peptides derived from the allergen sequence. The results showed that serum from immunized rabbits recognized three lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Of the 38 HDM allergen groups identified, allergens from 32 groups and 23 groups have been identified for Der f and Der p, respectively, and catalogued in the World Health Organization and International Union of Immunological Societies (WHO/IUIS) allergen database (http://www.allergen.org ). The most clinically important HDM allergens identified thus far have been group 1, group 2, and group 23 allergens [9 ], with recent evidence suggesting that HDM group 24 allergens may also be clinically important [10 ]. Previously, we found that a group 24 Der f allergen, namely Der f 24, was a ubiquinol cytochrome C reductase binding (UQCRB) protein homolog [10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 38 HDM allergen groups identified, allergens from 32 groups and 23 groups have been identified for Der f and Der p, respectively, and catalogued in the World Health Organization and International Union of Immunological Societies (WHO/IUIS) allergen database (http://www.allergen.org ). The most clinically important HDM allergens identified thus far have been group 1, group 2, and group 23 allergens [9 ], with recent evidence suggesting that HDM group 24 allergens may also be clinically important [10 ]. Previously, we found that a group 24 Der f allergen, namely Der f 24, was a ubiquinol cytochrome C reductase binding (UQCRB) protein homolog [10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bet v 1 dimerization provides two IgE binding sites that are required for cross-linking of IgE in effector cells and BCRs in B lymphocytes [56,60]. Interestingly, all these aforementioned dimeric allergens are known lipids carriers, as is rDer p 5 [16,19,26]. However, the investigation of IgE binding of a monomeric rDer p 5 in comparison with our oligomerized one would still be warranted, and we still believe that our IgE frequency was a relevant result.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, the number of monoclonal antibodies available for use in affinity chromatography is currently scarce, especially in the case of certain allergic sources [48,49]. For this reason, most research groups tend to heterologously express allergens and characterize them in vitro first [16,19,26]. With a few exceptions, most recombinant allergens displayed identical or similar allergenic activity and IgE binding capacity [43,45,50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations